The Ddc1-Mec3-Rad17 Sliding Clamp Regulates Histone-Histone Chaperone Interactions and DNA Replication-coupled Nucleosome Assembly in Budding Yeast - Burgess, Rebecca J. (American Society for Biochemistry and Molecular Biology, 2014)
The maintenance of genome integrity is regulated in part by chromatin structure and factors involved in the DNA damage response pathway. Nucleosome assembly is a highly regulated process that restores chromatin structure after DNA replication, DNA repair, and gene transcription. During S phase the histone chaperones Asf1, CAF-1, and Rtt106 coordinate to deposit newly synthesized histones H3-H4 onto replicated DNA in budding yeast. Here we describe synthetic genetic interactions between RTT106 and the DDC1-MEC3-RAD17 (9-1-1) complex, a sliding clamp functioning in the S phase DNA damage and replication checkpoint response, upon treatment with DNA damaging agents. The DNA damage sensitivity of rad17Δ rtt106Δ cells depends on the function of Rtt106 in nucleosome assembly. Epistasis analysis reveals that 9-1-1 complex components interact with multiple DNA replication-coupled nucleosome assembly factors, including Rtt106, CAF-1, and lysine residues of H3-H4. Furthermore, rad17Δ cells exhibit defects in the deposition of newly synthesized H3-H4 onto replicated DNA. Finally, deletion of RAD17 results in increased association of Asf1 with checkpoint kinase Rad53, which may lead to the observed reduction in Asf1-H3 interaction in rad17Δ mutant cells. In addition, we observed that the interaction between histone H3-H4 with histone chaperone CAF-1 or Rtt106 increases in cells lacking Rad17. These results support the idea that the 9-1-1 checkpoint protein regulates DNA replication-coupled nucleosome assembly in part through regulating histone-histone chaperone interactions.